Estudo da publicidade brasileira de produtos dirigida às crianças e a relação com as distorções cognitivas - Silveira, Sandra Maria Prado (2018)
The present work aims to investigate, through a proof of judges, whether there were any possible cognitive distortions in a transcript text of a piece of children advertisement related to the pharmacological market and broadcasted nationally in the mainstream media. Considering that professionals of the area of marketing and advertisement use numerous strategies aimed at consumerism, expansion of sales volume and generation of profit, it is assumed that, when trying to convince consumers, advertising messages and programs disseminate both maladaptative behavior and maladaptative beliefs. To verify if there were any distortions in the above-mentioned advertisement, a proof of judges was performed. To do so, eight judges, experienced in both academic and clinical cognitive-behavioral therapy, were invited to take part in this study. Six judges were female (75%) and two of them were male (25%), the average age being 31 years old, holding a Psychology degree not older than 8 years in average (DP 8,13). The judges evaluated both verbal and non-verbal transcriptions of a piece of children advertisement, followed by a table which contained the description of six cognitive distortions that might or might not be identified in the advertisement. The above-mentioned six distortions were named as: 1) The defeaters; 2) Exploding everything; 3) Foreseeing failure; 4) Experiencing thoughts; 5) Preparing to fail; 6) Blame me! The judges could also choose an option in which no distortions were present in the advertisement. The collected data was analyzed using the Kappa index (K) and the statistic results pointed to a very strong agreement related to the thinking error classified as “exploding everything”. It is known that techniques related to categorization, recording and reframing of thoughts are important in the process of cognitive therapy. Thus, some advertisements, when displaying thinking errors, may not only promote client resistance but also create difficulty in the therapeutic process. Therefore, the link between advertisement and cognitive distortion can be an important aspect to be taken into consideration and even included in sessions as an example of psycoeducation, exposing the child to the types of thoughts that must be avoided. Besides, broader and more complex studies can contribute to the regulation of children advertisement, taking into account the influence exerted by publicity in cognitive processing, as a way of avoiding thinking errors through media actions.